Theoretical report: reflections and considerations for authors, reviewers, and editors - Breno Augusto Bormann de Souza Filho; Érika Fernandes Tritany; Cláudio José Struchiner (Universidade de São Paulo, 2022)
ABSTRACT Epidemiological studies focused on public health have currently shown significant limitations regarding in-depth theoretical reports, overvaluing methodological aspects. The lack of theoretical explanation affects both the quality and reproducibility of studies. This study therefore reflected on the importance of in-depth theoretical reports considering the theoretical foundation used by researchers in the main sections of the manuscript (title, abstract, introduction, methodology, results, discussion, and conclusion) based on a review of the scientific literature on the subject. We believe that this article can help understand the importance and the development of in-depth theoretical reports in scientific articles, contributing to assessments, interpretations, and criticisms of reviewers and editors regarding the explanation and reporting of theoretical foundation in manuscripts submitted to scientific journals.